A safe, high fertilizer-efficiency and economical approach based on a low-volume spraying UAV loaded with chelated-zinc fertilizer to produce zinc-biofortified rice grains. (10th November 2021) - Xu, Meng; Liu, Mengjiao; Liu, Fan; Zheng, Nan; Tang, Sheng; Zhou, Jingjie; Ma, Qingxu; Wu, Lianghuan
Abstract: Agricultural spraying unmanned aerial vehicles (UAVs) can be used to avoid human exposure to agrochemical mists and to obtain many extra benefits in crop protection, and concentrated Zn fertilizer is needed for low-volume UAV sprays applied for Zn biofortification. Applying the widely used ZnSO4 fertilizer at high spraying rates improved Zn biofortification, but it also caused leaf burn, yield losses, and fertilizer losses. To determine whether there is an alternative UAV-supported Zn source that further improves Zn concentration in rice seeds without compromising agronomic performance, a 3-year field experiment was conducted. Initial tests at different spraying rates showed that Zn-EDTA, Zn-Gly, and Zn-Glc had approximately two-fold higher safe threshold rates (≤0.8%) than ZnSO4 and ZnNO3 . Furthermore, Zn biofortification was optimally improved by applying ZnNO3 at a normal rate, and Zn-Gly was the best at a high spraying rate. The third-year results demonstrated that two sprays of 0.81% Zn-Gly by UAV achieved equivalent Zn biofortification levels as those after three sprays of 0.27% ZnNO3 by manual spraying. In addition, UAV-based spraying greatly lowered the risk of fertilizer residual in rice paddies because of its low Zn input and its high Zn recovery rate. This safer and cleaner technology will expand the existing fertilizing options to produce highly Zn-biofortified grain with low input costs. Graphical abstract: Image 1 Highlights: ZnNO3 achieved greater Zn-biofortification than ZnSO4 . Excess spraying Zn rates damaged foliage and decreased yield of rice. Chelated Zn lowered the foliar phytotoxicity than excess inorganic Zn. Zn-Gly achieved the highest Zn-biofortification among chelated Zn sources. UAV-based spraying of Zn-Gly improved Zn recovery rate.